MENINGKATKAN MOTORIK KASAR MELALUI MEDIA PERMAINAN DARTS PADA ANAK USIA 5 – 6 TAHUN - Adam Maulana Hidayatullah (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2025)
The teacher's efforts in teaching students are a very important part in achieving the success of the planned learning objectives. Therefore, choosing the right media, methods, strategies, approaches and techniques is the most important element carried out by the class teacher because the teacher is the one who knows better the condition of his students. For this reason, research is needed to improve learning. This learning improvement research was carried out on learning gross motoric concepts using the media game darts in children aged 5 - 6 years at PAUD Nurul Anwar, Pontang District, Serang Regency. Improvements were made because the results of learning to describe children's gross motor skills were still low. This is due to the use of inappropriate learning media. The aim of this improvement is to improve gross motor skills using Media Darts. Children's learning outcomes increase after teachers use appropriate media that is integrated with gross motor learning methods, such as: Lecture Method, Discussion Method, Assignment Method, etc. The success score achieved by 13 students out of a total of 15 students was 90%, 10% greater than the target for complete student learning outcomes of 80% in cycle 2.